Assessing the Effects of COVID-19 on Restaurant Business From Restaurant Owners’ Perspective - Sardar, Sazu; Ray, Rudrendu; Hasan, Md. Kamrul; Chitra, Shital Sohani; Parvez, A. T. M. Shahed; Avi, Md. Ashikur Rahman (Frontiers in Psychology, 2022)
Purpose – The main purpose of this study is to assess the effects of COVID 19 on the restaurant businesses of Bangladesh. It examines the socio-economic impacts of the compassionate disaster COVID 19 pandemic from the perspective of the restaurant owners. The study also purposes to provide recommendations to mitigate the effects on the restaurant business. Design/methodology/approach – A qualitative research approach was adopted to explore the effects of the COVID 19 pandemic on the restaurant businesses of Bangladesh. A total of 22 in-depth interviews were conducted with the top-ranked restaurant owners in the Rajshahi City Corporation area of Bangladesh. Thematic analysis technique was applied for analyzing the collected data. Findings – The study found that the restaurant owners were compelled to reduce their number of employees, forced to ensure social distancing and proper sanitization which increased the expenses. Although online orders and home delivery services have increased significantly, restaurant business operation is gradually turning critical owing to the lack of financial support. Thus, restaurant owners urged for financial assistance from the government. Research limitations/implications – Since this research only focused on one city in Bangladesh, the outcomes of the study may have a dearth of generalizability. Hence, the investigators are encouraged to extend the study area. Practical implications – This study will help restaurant owners and policymakers in formulating contemporary business policies and strategies. Thus, it will be supportive to improve the present condition of the restaurant businesses in developing countries like Bangladesh. Originality/value – This paper identified the truculent scenario of the restaurant business during the COVID 19 pandemic. Article Type: Research paper